Linguistic Analysis: Humorous English Erotic Jokes in an Instagram Account - Setiawan, Budi Rahmat (Research Community for Critical Society and Environment, 2025)
Humor is essential to make something forbidden or taboo acceptable. One example can be seen in sexual acts/relationships. It can only be acceptable to be talked out loud when it is used as joking material. Joking can only be done if the speaker or the hearer has the competence of telling and understanding jokes. Jokes also can only be understood in some contexts. In telling jokes, the speaker must follow and understand some maxims by Grice. It is because violating the joking mode of maxims can make the joke fail to be understood. This research tries to analyze erotic jokes found in an Instagram account @tarablairball. It is descriptive-qualitative research that tries to revisit and compare this analysis by doing similar research to Wijana (2022). The data taken are 80 first erotic jokes since she first made content about it. From the analysis of 80 erotic jokes found in the data source. There are some categories of jokes from the perspective of linguistics. It is found that there are 29 metaphors, 28 Slang, 11 Polysemies, 2 Homophones, 2 Metonymies, and 2 Sound Changes. In addition, there are 3 homonyms found. The study is expected to be useful for future studies related to humor and pragmatics.